Iron oxide and various metal oxide nanotubes engineered by one-pot double galvanic replacement based on reduction potential hierarchy of metal templates and ion precursors. Issue 63 (20th October 2020) - Paragodaarachchi, Aloka; Medvedovsky, Steven; Fang, Justin; Lau, Timothy; Matsui, Hiroshi
Abstract : A one-pot double galvanic approach was explored for the rational synthesis of a variety of metal oxide nanotubes from Ag nanowire substrates, predictable based on the reduction potential hierarchy of the templates and ion precursors. Abstract : A one-pot double galvanic approach was explored for the rational synthesis of metal oxide nanotubes, predictable based on the reduction potential hierarchy of templates and ion precursors ( e.g., Ag nanowire substrate is oxidized by MnO4 − ions and it is consecutively reduced by Fe 2+ ions to form an Fe2 O3 nanotube). This method generated a variety of metal oxide nanotubes via a redox potential landscape.